Reproduction in dwarf chameleons (Bradypodion) with particular reference to B. pumilum occurring in fire-prone fynbos habitat - Jackson, Jennifer C. (Jennifer Claire) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2007.